Dragons, brimstone and the geology of a volcanic arc on the island of the last Samurai, Kyushu, Japan. (27th January 2016) - Williams, Mark; Wallis, Simon; Komatsu, Toshifumi; Tanaka, Gengo; Oji, Tatsuo; Clark, Nicola
Abstract : Not even Hollywood could dream of a place so magical as Kyushu. The southern‐most of the four major islands of the Japanese archipelago, this is a land of volcanoes, dinosaurs, and the last stand of the Samurai. And for good measure, James Bond visited here too, in the 1967 film You Only Live Twice . The final explosive scenes of that film featured the destruction of megalomaniac Ernst Stavro Blofeld's headquarters hidden inside the crater of one of Kyushu's most emblematic volcanoes, Shinmoedake. Kyushu also straddles the largest geological structure in Japan, the Median Tectonic Line (MTL) that runs from the western approaches of the island to the central part of Honshu. The MTL has been active since the Cretaceous, and the sedimentary basins formed along its line in Kyushu contain some of Japan's most famous dinosaur finds. The MTL also defines a fundamental divide between the geological histories of the terranes north and south of its line, a history that takes us back to the origins of the Japanese archipelago half a billion years ago.